Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Pencegahan Seksual Remaja Di SMA Ferdy Ferry Kota Jambi Tahun 2017 - Badriyah, Lailatul; Muntaha, Amar; Kesuma, Rismala (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
Period begins by puberty the period of change of physical change such us body shape physiological functions. Pychological changes. At the time teenagers include emotional changes.that changes like condition sensitive like easy to laughing for no reason. This research aiming for is knowing factors influencing behavior prevention sexsual teenagers in senior high school Ferdy Ferry Jambi City. Design this research in kuantitatif with use method survey analytic with like be closer cross sectional. Population this research as much 99 person. Sample this research as much 99 respondent with tecnic Purposive Sampling. Analysis this data do with analysis univariat, bivariat use test Chi-Square (a=0,05) and multivariat with use metode Regresi Logistic.          Result analyst univariat obtained for age 58,6%, gender 55,6%, knowledge 69,7%, attitude 67,7% and the role of parent 67,7% for sexsual behavior 72,7% thats good result analysis bivariat this factor for age (p=0,032), gender (p=0,012), knowledge (p=0,034), attitude (p=0,021), and the role of parent (p=0,021). This analysis result multivariat can thats gender is influence for teenager sexsual.         This result can concluded that there is take effect for age, gender, attitude and the role of parent. Suggested for school enter healt material reproduction to school study so that can being additional lessons os school extracurricular.